2022
DOI: 10.1093/oncolo/oyac036
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-based Radiomics in the Era of Immuno-oncology

Abstract: The recent, rapid advances in immuno-oncology have revolutionized cancer treatment and spurred further research into tumor biology. Yet, cancer patients respond variably to immunotherapy despite mounting evidence to support its efficacy. Current methods for predicting immunotherapy response are unreliable, as these tests cannot fully account for tumor heterogeneity and microenvironment. An improved method for predicting response to immunotherapy is needed. Recent studies have proposed radiomics—the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 128 publications
0
12
0
Order By: Relevance
“…The use of machine learning based blood biomarkers, such as neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio, have already been shown promising results in for patient selection and predicting the treatment outcome in non-small cell lung cancer patients treated with nivolumab ( 104 ). There is, moreover, an increasing interest in radiomics models trained the clinical outcomes ( 105 ). Radiomics uses large numbers of features extracted with data characterization algorithms from medical imaging to define tumor patterns and features that are not visible to the human eye.…”
Section: Current Challenges Further Directions and Potential Imaging ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of machine learning based blood biomarkers, such as neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio, have already been shown promising results in for patient selection and predicting the treatment outcome in non-small cell lung cancer patients treated with nivolumab ( 104 ). There is, moreover, an increasing interest in radiomics models trained the clinical outcomes ( 105 ). Radiomics uses large numbers of features extracted with data characterization algorithms from medical imaging to define tumor patterns and features that are not visible to the human eye.…”
Section: Current Challenges Further Directions and Potential Imaging ...mentioning
confidence: 99%
“…The field of radiomics may also offer additional information for the prediction of prognosis in patients treated with immunotherapy based on established molecular biomarkers ( 73 , 105 ). A recent multi-center retrospective study of large populations of non-small cell lung cancer patients demonstrated the utility of a deep learning score based on radiomics features extracted from 18 F-FDG-PET/CT to predict the PD-L1 expression status on immunohistochemistry ( 73 ).…”
Section: Current Challenges Further Directions and Potential Imaging ...mentioning
confidence: 99%
“…The identification of “ideal biomarkers” is considered a daunting task for many diseases, including some cancer types. Most of the current sampling techniques for cancer tissues cannot identify individuals who will lack response to therapy, and they fall short in classifying cancer types correctly, owing to the inter- and intra-tumor heterogeneity of tumors [ 80 ]. A biomarker should be easily measurable, non-invasive, and cost-effective.…”
Section: The Rationale For Microbiome-based Disease Biomarkersmentioning
confidence: 99%
“…Recently, some clinical trials have used diverse approaches to define characteristics of the patients who develop primary or acquired resistance to immunotherapy (e.g., NCT04243720) [ 168 ]. Such trials are aiming to develop an integrated model to predict drug resistance relying on multimodal data including radiomics, genomics, transcriptomics, epigenetics, immunophenotypic data, and fecal microbiome data [ 80 ]. There is promise that artificial intelligence models combining microbiome-based biomarkers with other omics data (e.g., radiomics) will be able to provide a more comprehensive view of the tumor microenvironment, aiding in better cancer diagnosis and allowing clinicians to non-invasively track changes in cancer phenotypes [ 80 ].…”
Section: Association Predictions Of Microbiome and Other Omics Datamentioning
confidence: 99%
“…An accurate assessment of preoperative RANKL levels may also help clinicians and patients make treatment decisions, including the determination of whether drug therapy, extended resection, postoperative radiotherapy, intensive follow-up, and reasonable clinical expectations. Although tissue biopsy before surgery can be used for disease detection, aside from invasive risk, a small amount of biopsy tissue cannot be used enough to evaluate the entire tumor heterogeneity, and making assessments based solely on small tissue biopsies can lead to bias in diagnosis and evaluation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%